2017
DOI: 10.6004/jnccn.2017.0120
|View full text |Cite
|
Sign up to set email alerts
|

A Practice-Based Evaluation of Distress Screening Protocol Adherence and Medical Service Utilization

Abstract: This study examined the extent to which cancer programs demonstrated adherence to their own prescribed screening protocol, and whether adherence to that protocol was associated with medical service utilization. The hypothesis is that higher rates of service utilization are associated with lower rates of adherence to screening protocols. Oncology social workers at Commission on Cancer-accredited cancer programs reviewed electronic health records (EHRs) in their respective cancer programs during a 2-month period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 29 publications
3
66
0
Order By: Relevance
“…Cancer October 15, 2018 in 55 cancer centers indicated that less than two-thirds of patients were screened. 52,54,55 The psychosocial literature indicates that screening for psychological distress may be inadequate, 56 and it is particularly difficult to screen for a low-incidence outcome like suicide. 57 Furthermore, many physicians may not be comfortable discussing psychosocial issues like suicide with patients or their relatives.…”
Section: Clinical and Public Health Implicationsmentioning
confidence: 99%
“…Cancer October 15, 2018 in 55 cancer centers indicated that less than two-thirds of patients were screened. 52,54,55 The psychosocial literature indicates that screening for psychological distress may be inadequate, 56 and it is particularly difficult to screen for a low-incidence outcome like suicide. 57 Furthermore, many physicians may not be comfortable discussing psychosocial issues like suicide with patients or their relatives.…”
Section: Clinical and Public Health Implicationsmentioning
confidence: 99%
“…There are no regulations about the number of sessions patients have the right to, and thus the number of sessions might be rather high, especially compared to countries with different health insurance systems (eg, the United States) and with less funded social work services at hospitals. Furthermore, Swedish OSWs are usually not involved in discharge planning or screening patients for distress, which seem to constitute important functions of OSWs in other countries . Instead, the main function of Swedish OSWs consists of providing psychosocial support and counselling .…”
Section: Introductionmentioning
confidence: 99%
“…As not all patients who receive a referral actually follow through with the referral, patients who do take up treatment should be followed separately from those who do not. In addition to researching the effects of distress screening, referral, and take up of services, future studies should also investigate possible reduction in utilization of medical services and associated costs [25].…”
Section: Discussionmentioning
confidence: 99%